[…] and he said those are picturebook horses and went on eating, des frontières du discours aux confins du récit : remarques sur l’usage du discours rapporté dans All The Pretty Horses de Cormac McCarthy - Christine COPY (E-REA)
The aim of the article is to assess the role of reported speech in the construction of fiction and in the expression of style in All the Pretty Horses by Cormac McCarthy. The approach consists in analyzing the linguistic features of reported speech to account for the role they play in the implementation of the novelistic project and the author’s style. In the specific case of All the Pretty Horses, those features are analyzed as related to the central theme of the border and its blurring as displayed in the novel. Relying on a quantitative and qualitative study of the verbs used to introduce reported speech, with a special focus on direct speech, two main issues are tackled: i) the role played by the verb type, the place (initial, central, final) and the word order (Subject-Verb / Verb-Subject) of reporting clauses in the expressivity of the text; ii) the relationship between the form of the reporting clauses and the seemingly objective mode of discourse thus implemented leading to a blurring of the distinction between discourse and narration. The study of these specificities exposes the relationship between the singular uses of linguistic forms and the achievement of an aesthetic project.